Faktor-faktor yang Memengaruhi Tingkat Kepuasan Petani Kelapa Sawit Plasma Terhadap Pola Kemitraan PT. Palma Megah Mulia di Desa Kersik Belantian Kecamatan Jelimpo - Fidiawati, Fidiawati; Yurisinthae, Erlinda; Hutajulu, Josua Parulian (Universitas Galuh, 2025)
The objective of this research is to analyze the satisfaction level of plasma oil palm farmers by assessing the attributes of the partnership model and to examine the factors influencing the satisfaction level of plasma oil palm farmers with the partnership model of PT. Palma Megah Mulia in Desa Jelimpo, Kecamatan Kersik Belantian. The sample in this study consisted of 42 respondents. This research was conducted using quantitative data. The tool used for analysis is the Customer Satisfaction Index (CSI) method, which is utilized to analyze the satisfaction level of plasma oil palm farmers by evaluating the partnership model attributes. Additionally, Multiple Linear Regression analysis was performed to identify the factors affecting the satisfaction level of plasma farmers with the partnership model. The results showed that the satisfaction level of farmers using the Customer Satisfaction Index (CSI) analysis was 86.67%, indicating that plasma oil palm farmers are highly satisfied with the partnership model of PT. Palma Megah Mulia. There is a significant influence of the satisfaction level of plasma oil palm farmers on the variables of age, education level, frequency of socialization, and land area on the partnership model of PT. Palma Megah Mulia. Based on the findings of the research, it is recommended that the Company increase socialization activities so that the understanding of plasma farmers about partnership patterns is better.